A systematic literature review of granulocytes-colony stimulating factor treatment in animals - AHMAD AFFANDI, SYAHIRAH; KHAIRUDDIN, NURUL HAYAH; BABATUNDE, MOHAMMED SADIQ; OTHMAN, AZALEA HANI; SENG KIM, COLLIN LOOI; OTHMAN, SITI SARAH; SYED WASEEM AHMAD, SHARIFAH ROOHI (2024)
This study presents a systematic literature review (SLR) on the efficacy of granulocytes-colony stimulating factor (G-CSF) as a treatment component in relation to clinicopathological parameters and overall outcomes. Using the PICO approach, a research question development tool, the SLR was designed to identify the animals in which G-CSF had been used, the types of G-CSF utilized and their effectiveness as a therapeutic agent in stimulating haematological parameters, as well as their potential adverse effects. Three primary keywords associated with the review topic were selected and incorporated into the search query to retrieve pertinent literature from three databases: Scopus, Science Direct, and CAB Direct. A total of 17 articles on G-CSF, published between 2018 and 2023, and fulfilling the inclusion criteria were comprehensively analyzed. Diverse G-CSFs were utilized in treatment protocols ranging from short-acting to long-acting preparations, as well as heterologous or species-specific G-CSFs. The administration of G-CSF treatment in animals increases the overall count of white blood cells (WBC) with no adverse reaction, except a temporary decrease in platelet levels in a feline subject and a reduction in RBC counts in bovine and ovine subjects. Only a few studies have investigated the impact of G-CSF on the red blood cell (RBC) parameters in animals. Current research gaps were identified, for advancement of knowledge and to aid researchers in identifying research opportunities, designing future studies, and generating corresponding suggestions or ideas.